2016
DOI: 10.3324/haematol.2016.143891
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of microRNA and microRNA-regulated messenger RNA expression in germinal center B-cell lymphomas determined by integrative sequencing analysis

Abstract: MicroRNA are well-established players in post-transcriptional gene regulation. However, information on the effects of microRNA deregulation mainly relies on bioinformatic prediction of potential targets, whereas proof of the direct physical microRNA/target messenger RNA interaction is mostly lacking. Within the International Cancer Genome Consortium Project "Determining Molecular Mechanisms in Malignant Lymphoma by Sequencing", we performed miRnome sequencing from 16 Burkitt lymphomas, 19 diffuse large B-cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…Although some differences in coding gene expression profiles have also been described between FL1‐2 and FL3A, these FL subtypes are also closely related, as also shown at the genetic and immunohistochemical level (Horn et al , ). Non‐coding RNA expression profiling studies in FL have basically analysed expression and sequence alterations of microRNAs (Musilova & Mraz, ; Hezaveh et al , ). A recent pilot study comparing three FL3A cases to reactive lymph nodes identified four lncRNAs overexpressed in the tumour samples, suggesting that these transcripts may be relevant in these tumours (Pan et al , ).…”
mentioning
confidence: 99%
“…Although some differences in coding gene expression profiles have also been described between FL1‐2 and FL3A, these FL subtypes are also closely related, as also shown at the genetic and immunohistochemical level (Horn et al , ). Non‐coding RNA expression profiling studies in FL have basically analysed expression and sequence alterations of microRNAs (Musilova & Mraz, ; Hezaveh et al , ). A recent pilot study comparing three FL3A cases to reactive lymph nodes identified four lncRNAs overexpressed in the tumour samples, suggesting that these transcripts may be relevant in these tumours (Pan et al , ).…”
mentioning
confidence: 99%
“…As there is no list of previously defined miRNA driver genes, we could not formally validate our approach; however, among the top-scored overmutated miRNA genes, we identified hsa-miR-142, which is the only miRNA gene in which mutations were identified in several hematologic neoplasms in several studies [49][50][51][52][53]56,57 , and their cancer relevance was functionally confirmed 27 . Our analysis confirmed the recurrence of hsa-miR-142 mutations in hematologic neoplasms, i.e., LAML, DLBC, and also the newly identified mutation in the Burkitt lymphoma Raji cell line, but also showed mutations in several solid tumors, i.e., UCEC, BLCA, GBM, and BRCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-142 is, to the best of our knowledge, the only miRNA gene convincingly shown to be recurrently mutated in several neoplasms, which include acute myeloid leukemia (AML) 49,50 and different types of B-cell lymphoma 51,52 , chronic lymphocytic leukemia (CLL) 53 and diffuse large-cell B-cell lymphoma [54][55][56][57] . Additionally, in our sequencing analysis performed within the framework of other projects, we found also one mutation in the seed region of hsa-miR-142 (chr17:58331263C>T[-]) in the Raji Burkitt lymphoma cell line (out of 5 Burkitt's lymphoma cell lines tested) (Fig.…”
Section: Hsa-mir-142mentioning
confidence: 99%
“…Additionally, miRNA genes are often either amplified or deleted in cancer in a similar fashion as protein coding oncogenes and tumor suppressor genes, and somatic copy number variation may be an important mechanism underlying aberrant miRNA expression in cancer (15,32,33) In contrast to the excitement about the role of miRNA in cancer, very little is known about somatic mutations in miRNA genes (defined here as sequences encoding pre-miRNAs and their directly adjacent flanks; note that actual miRNA genes are much larger, encoding entire transcription units) in cancer. Important exceptions are (i) a recently published study reporting a tool (ADmiRE) for the annotation and prioritization of different genetic variants, including somatic mutations in miRNAs (34), (ii) a database of somatic mutations affecting the interactions of miRNAs with competing endogenous RNAs (SomamiR), including somatic mutations in miRNAs (35), and (iii) recent reports of somatic mutations in pre-miR-142 (the only example of recurrently mutated miRNA gene in cancer), shown to contribute to the development of diffuse large B-cell lymphoma, follicular lymphoma and acute myeloid leukemia (36)(37)(38).…”
Section: Introductionmentioning
confidence: 99%